EFFECTS OF ALTERNATE STARVATION AND RE-FEEDING CYCLES ON COMPENSATORY GROWTH RESPONSE IN CYPRINUS CARPIO AND CIRRHINUS MRIGALA: A COMPARATIVE STUDY - LANGER, SEEMA; SHARMA, CHETNA; DEVI, ARTI (Journal of the Inland Fisheries Society of India, 2022)
A comparative study was conducted to evaluate the effect of feed cycling and ration level on the compensatory growth of Cirrhinus mrigala and Cyprinus carpio. Fingerlings of Cirrhinus mrigala and Cyprinus carpio were randomly collected from Nowabad Fish Farm and divided into control, 1week, 2 week and 3 week feed cycling groups. No hyperphagy occurred in Cirrhinus mrigala and Cyprinus carpio during re-feeding periods. ‘3 and 3’ feeding cycle group with 5% ration level performed better than ‘2 and 2’ and ‘1 and 1’ feeding cycle groups in case of Cirrhinus mrigala and ‘1 & 1’ feeding cycle group with 5% ration level performed better than ‘2 & 2’ and 3 & 3’ feeding cycle group in case of Cyprinus carpio. However, final results suggested that growth parameters were significantly different (P